The Participation Of Psycholinguistic Models In Literary Translation - Nafisa Kasimova (Genius Journals, 2023)
This article deals with the interaction between the psycholinguistic models and the process of literary translation. By examining the cognitive mechanisms that underlie language processing and creativity, we aim to shed light on the ways in which psycholinguistic factors influence the translator's choices when conveying literary expressions across languages. Drawing on a synthesis of literature in psycholinguistics and translation studies, we employ a multidisciplinary approach to investigate the methods, results, and implications of the participation of psycholinguistic models in literary translation
Keywords: psycholinguistics; literary translation; cognitive processes; creativity